Quality of life among dentists in teaching hospitals in South Canara, India - Dolar Doshi; Animesh Jain; K Vinaya; Shashidhar Kotian (Wolters Kluwer Medknow Publications, 2011)
Objectives : This paper reports on the quality of life among dentists using World Health Organization Abbreviated Instrument for Quality of Life Assessment, comprising 26 items which measure the following broad domains: Physical health, psychological health, social relationships, and environment. Materials and Methods : The instrument was self-administered among dentists in four teaching dental institutions. A total of 191 questionnaires were given out. Of those, 187 were consented and answered, making up a response rate of 97.9%. The internal consistency of the questionnaire, measured by Cronbach's alpha was estimated at 0.75. Results : Highest mean score was seen for Domain 3 (Social relationships) (16.15 + 2.38) and the least score was for Domain 4 (Environment) (14.72 + 2.12). Higher proportions of respondents rated their quality of life as good (65.1 percent), and also majority of dentists (63.5 percent) were satisfied with their health. Conclusion : Quality of life recognizes the value of an individual's health in the broader psychologic and social aspects of his/her life. In this study, the overall rating of quality of life among dentists in teaching hospitals is good.